2010
DOI: 10.1111/j.1439-0434.2009.01629.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, Biological and Phylogenetic Analysis of Chinese Isolates ofHop stunt viroidAssociated with Citrus Cachexia Disease

Abstract: Citrus cachexia is an economically important disease of citrus hosts caused by specific variants of Hop stunt viroid (HSVd) that are usually referred to as Citrus cachexia viroid (CCaVd). Eight cachexia-associated HSVd isolates were collected from six citrus growing areas of China, where citrus cachexia had not been reported previously. Forty-seven independent cDNA clones were used for genetic diversity and phylogenetic analysis. There were no sequence variant-cultivar correlation and no distinct regional spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Interestingly, one clone (HSVd1.7) had 100% identity compared with cachexia variant from Japan (AB211242). In addition, the same variant was recently reported in China (FJ716175) (Wang et al, 2010), Iran (GQ246200) and Spain.…”
Section: Phylogenetic Analysissupporting
confidence: 70%
See 1 more Smart Citation
“…Interestingly, one clone (HSVd1.7) had 100% identity compared with cachexia variant from Japan (AB211242). In addition, the same variant was recently reported in China (FJ716175) (Wang et al, 2010), Iran (GQ246200) and Spain.…”
Section: Phylogenetic Analysissupporting
confidence: 70%
“…A second cluster, formed by CVd-IIa group, contained 2 cDNA clones from Washington navel isolate, two clementine variant previously reported by Elleuch et al (2006) and two other variants recently reported by Wang et al (2010). Four cDNA clones (17F-HSV, 16F-HSV, HSVd1.5 and HSVd2.6) clustered in CVd-IIc group.…”
Section: Phylogenetic Analysismentioning
confidence: 66%
“…So far, the molecular characteristics and evolutionary analysis of several citrus viroids have been reported [ 14 , 28 , 31 33 ]. In this study, CBCVd-LSS was detected in six citrus cultivars from Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence for the Near East origin of CVds has been found in the People's Republic of China, where tests conducted in the late 1970s showed that only imported citrus varieties were infected with viroids (e.g., CEVd and HSVd; Wang et al 2010). This was easy to determine as all varieties were propagated on widely planted trifoliate orange and Satsuma, both of which showed no symptoms of exocortis (Broadbent et al 1979;P Barkley, personal communication).…”
Section: Xyloporosis-cachexia: the Connection To The Hop Stunt Viroid A Ubiquitous Pathogen Of Fruit Treesmentioning
confidence: 98%